Juvenile Court Outcomes for Retail Offenders: An Examination of Offense Type, Sex, and Race/Ethnicity - Elligson, Richard L. (Crime & delinquency, 2022)
Using all delinquency referrals in a Northeast state, the current study examined how youth charged with retail offenses differed from other offense types across multiple juvenile court outcomes (i.e., petition, adjudication, and disposition). The individual and joint effects of a juvenile?s sex and race/ethnicity were also investigated to determine whether these extralegal factors conditioned the relationship between offense type and juvenile system processing. Findings indicate that at each decision-making stage, retail offenders were significantly more likely to be treated with leniency compared to other offense types. The results also reinforced the continued impact of sex and race/ethnicity on shaping judicial outcomes at each stage. Implications regarding the processing of juvenile retail offenders and the influence of juvenile characteristics on juvenile court decision-making are discussed.